2022
DOI: 10.14812/cuefd.947383
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Views on Initial Literacy Teaching in the Distance Education Process

Abstract: The aim of this study was to determine the views of parents of primary school 1st grade children regarding their experiences in primary literacy teaching in the distance education process. For this purpose, qualitative phenomenology was used as a research design. The study group of the research consists of 76 parents of students studying in the firstgrade branches of two different primary schools affiliated to the Ministry of National Education. The data of the study were collected with a standardized intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Te research results showed that when designing the content and form of the professional development plan, priority should be given to the diferences in text use and interpretation of diferent school subjects to better support subject teaching [1]. Te purpose of Ilhan's and Kesik's research was to determine the parents' views on their experience of primary school literacy teaching in distance education [2]. Gezer Melike proposed that early literacy skills are all prerequisite knowledge, skills, and attitudes necessary for successful reading and writing during formal education.…”
Section: Introductionmentioning
confidence: 99%
“…Te research results showed that when designing the content and form of the professional development plan, priority should be given to the diferences in text use and interpretation of diferent school subjects to better support subject teaching [1]. Te purpose of Ilhan's and Kesik's research was to determine the parents' views on their experience of primary school literacy teaching in distance education [2]. Gezer Melike proposed that early literacy skills are all prerequisite knowledge, skills, and attitudes necessary for successful reading and writing during formal education.…”
Section: Introductionmentioning
confidence: 99%